SISTEM PEMBIAYAAN BERDASARKAN PRINSIP SYARIAH (Suatu Tinjauan Yuridis Terhadap Praktek Pembiayaan di Perbankan Syariah di Indonesia) - Supriyadi, Ahmad (Al-Mawarid Jurnal Hukum Islam, 2003)
This research aims at knowing sub system of law about the finance based on Syariah principle in Indonesia by method normative judicial approach not Islamic jurisprudence approach because the dispute finance have to solve by civil law of Indonesia. The research shows that finance based on Syariah principle have sub systems are profit sharing system, sale system and lease system.